2006
DOI: 10.1124/jpet.106.111062
|View full text |Cite
|
Sign up to set email alerts
|

Agonist and Antagonist Effects of 15R-Prostaglandin (PG) D2and 11-Methylene-PGD2on Human Eosinophils and Basophils

Abstract: Prostaglandin (PG) D 2 acts through both the DP 1 receptor, which is coupled to adenylyl cyclase, and the DP 2 receptor (chemoattractant receptor-homologous molecule expressed on Th2 cells), which is present on eosinophils, basophils, and Th2 cells and results in cell activation and migration. The most potent prostanoid DP 2 agonist so far reported is 15R-methyl-PGD 2 , in which the hydroxyl group has the unnatural R configuration. In contrast, the corresponding analog possessing the natural 15S configuration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
0
16
1
Order By: Relevance
“…S3). For example, the weak agonist 11-deoxy-11-methylene PGD 2 (28) had the lowest activity (hair growth inhibition) of the compounds tested. Note that GPR44 has nanomolar affinities for ligands, but as is typical for this type of experiment, higher concentrations were required to overcome tissue penetration and compound lysis.…”
Section: Resultsmentioning
confidence: 99%
“…S3). For example, the weak agonist 11-deoxy-11-methylene PGD 2 (28) had the lowest activity (hair growth inhibition) of the compounds tested. Note that GPR44 has nanomolar affinities for ligands, but as is typical for this type of experiment, higher concentrations were required to overcome tissue penetration and compound lysis.…”
Section: Resultsmentioning
confidence: 99%
“…An important role for DP 2 receptors in chronic cutaneous inflammation was revealed in DP 2 -deficient mice (Satoh et al, 2006). Prostaglandin D 2 also activates basophils via DP 2 receptors (Hirai et al, 2001;Cossette et al, 2007). A final comment on the roles of DP 1 and DP 2 in regulating allergy/inflammation Pettipher, 2008): the employment of a DP 2 antagonist may switch PGD 2 from a pro-to an antiinflammatory mediator in many instances.…”
mentioning
confidence: 99%
“…The 15S stereochemistry is atypically not crucial to DP 2 agonism, with 15R-and 15R-15-methyl PGD 2 showing high DP 2 /DP 1 selectivity (Jones, 1976(Jones, ,a,b, 1978Monneret et al, 2001Monneret et al, , 2003Kim et al, 2005;Cossette et al, 2007). Moreover, 15-oxo structures (usually considered to be bioinactive products of 15-hydroxy PG dehydrogenase) retain high DP 2 agonism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Especially isomers from the F-ring (dihydroxypentan) class have been investigated extensively. However, recent studies also showed that isomers from the Dand E-ring group (hydroxypentanon) can serve as biomarkers and bioactive substances (Cossette et al, 2007;Brose et al, 2011).…”
Section: Discussionmentioning
confidence: 98%